Ag1Pd1 Nanoparticles–Reduced Graphene Oxide as a Highly Efficient and Recyclable Catalyst for Direct Aryl C−H Olefination. Issue 70 (10th October 2017) - Hu, Qiyan; Liu, Xiaowang; Wang, Guoliang; Wang, Feifan; Li, Qian; Zhang, Wu
Abstract: The efficient and selective palladium‐catalyzed activation of C−H bonds is of great importance for the construction of diverse bioactive molecules. Despite significant progress, the inability to recycle palladium catalysts and the need for additives impedes the practical applications of these reactions. Ag1 Pd1 nanoparticles–reduced graphene oxide (Ag1 Pd1 ‐rGO) was used as highly efficient and recyclable catalyst for the chelation‐assisted ortho C−H bond olefination of amides with acrylates in good yields with a broad substrate scope. The catalyst can be recovered and reused at least 5 times without losing activity. A synergistic effect between the Ag and Pd atoms on the catalytic activity was found, and a plausible mechanism for the AgPd‐rGO catalyzed C−H olefination is proposed. These findings suggest that the search for such Pd‐based bimetallic alloy nanoparticles is a new method towards the development of superior recyclable catalysts for direct aryl C−H functionalization under mild conditions. Abstract : Direct aryl C−H activation catalyzed by supported bimetallic alloy nanoparticles is described. Ag1 Pd1 ‐rGO can be used as a highly efficient and recyclable catalyst for ortho C−H olefination of amides with acrylates in good yields under base‐free and additive‐free conditions in air.